TOKSISITAS EKSTRAK METANOL DAUN KETAPANG (Terminalia catappa) TERHADAP LARVA Artemia salina Leach MENGGUNAKAN METODE Brine Shirmp Lethality Test (BSLT) - Alfin Surya (LPPM Universitas Abdurrab, 2018)
Ketapang leaves is one of the traditional medicine ingredients that can cure various diseases such as insomnia, liver, cardiovascular and respiratory. Previous scientific research states that ketapang leaves contain flavonoids, fenolix and saponins. This study aims to determine the toxicity of ketapang leaf methanol extract using Brine Shrimp Lethality Test (BSLT) method. The extract was prepared by maceration using methanol solvent. Toxicity test was performed using 48-hour Artemia salina Leach shrimp larvae. Toxic effects of the extract were identified with the percentage of shrimp larvae mortality using probit analysis (LC50). Ketapang leaves contain phytochemicals including flavonoids and saponins. This research shows that ketapang leaf extract is very toxic (LC50 of 56 ppm) so it can be used as medicine material.